2018
DOI: 10.1002/art.40439
|View full text |Cite
|
Sign up to set email alerts
|

Long‐Term Safety and Efficacy of Belimumab in Patients With Systemic Lupus Erythematosus

Abstract: ObjectiveWe undertook this US multicenter continuation study (GlaxoSmithKline study BEL112233; ClinicalTrials.gov identifier: NCT00724867) to assess long‐term safety and efficacy of belimumab in patients with systemic lupus erythematosus (SLE) who completed the Study of Belimumab in Subjects with SLE 76‐week trial (ClinicalTrials.gov identifier: NCT00410384).MethodsPatients continued to receive the same belimumab dose plus standard therapy; patients previously receiving placebo received 10 mg/kg belimumab. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 72 publications
(24 citation statements)
references
References 25 publications
2
14
0
5
Order By: Relevance
“…The largest improvements in HRQoL and fatigue were reported in the first study year of treatment and were maintained or further increased during long‐term exposure to belimumab through study year 6. Previously reported efficacy and safety data from this long‐term continuation study demonstrated an overall decrease in disease activity, along with a decrease in prednisone use, low rates of flare, and organ damage accrual and an acceptable safety profile . Taken together, these results suggest that long‐term control of disease activity with belimumab plus standard therapy results in significant benefits in both HRQoL and fatigue.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…The largest improvements in HRQoL and fatigue were reported in the first study year of treatment and were maintained or further increased during long‐term exposure to belimumab through study year 6. Previously reported efficacy and safety data from this long‐term continuation study demonstrated an overall decrease in disease activity, along with a decrease in prednisone use, low rates of flare, and organ damage accrual and an acceptable safety profile . Taken together, these results suggest that long‐term control of disease activity with belimumab plus standard therapy results in significant benefits in both HRQoL and fatigue.…”
Section: Discussionsupporting
confidence: 60%
“…This was a multicenter continuation study (BEL112233; ClinicalTrials.gov identifier: NCT00724867) in patients with SLE who completed the 76‐week parent trial BLISS‐76 (BEL110751; ClinicalTrials.gov identifier: NCT00410384) in the US . In BLISS‐76, patients were randomized to receive belimumab 1 mg/kg intravenously (IV), 10 mg/kg IV, or placebo every 28 days and continued with standard therapy.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“… 13 15 Short-term (up to 76 weeks) efficacy and safety of belimumab have been demonstrated in four large Phase 3 clinical trials, 16 19 and these safety and efficacy profiles have recently been shown to be maintained up to 7 years of belimumab treatment. 20 Currently, belimumab is indicated as add-on therapy in adult patients with active, autoantibody-positive SLE despite standard therapy (ST) 11 and with a high degree of disease activity (e.g. positive anti-dsDNA and low complement levels).…”
Section: Introductionmentioning
confidence: 99%